Patterns in evolutionary origins of heme, chlorophyll a and isopentenyl diphosphate biosynthetic pathways suggest non-photosynthetic periods prior to plastid replacements in dinoflagellates - Matsuo,Eriko; Inagaki,Yuji (PeerJ, 2018)
Background The ancestral dinoflagellate most likely established a peridinin-containing plastid, which have been inherited in the extant photosynthetic descendants. However, kareniacean dinoflagellates and Lepidodinium species were known to bear “non-canonical” plastids lacking peridinin, which were established through haptophyte and green algal endosymbioses, respectively. For plastid function and maintenance, the aforementioned dinoflagellates were known to use nucleus-encoded proteins vertically inherited from the ancestral dinoflagellates (vertically inherited- or VI-type), and those acquired from non-dinoflagellate organisms (including the endosymbiont). These observations indicated that the proteomes of the non-canonical plastids derived from a haptophyte and a green alga were modified by “exogenous” genes acquired from non-dinoflagellate organisms. However, there was no systematic evaluation addressing how “exogenous” genes reshaped individual metabolic pathways localized in a non-canonical plastid. Results In this study, we surveyed transcriptomic data from two kareniacean species (Karenia brevis and Karlodinium veneficum) and Lepidodinium chlorophorum, and identified proteins involved in three plastid metabolic pathways synthesizing chlorophyll a (Chl a), heme and isoprene. The origins of the individual proteins of our interest were investigated, and we assessed how the three pathways were modified before and after the algal endosymbioses, which gave rise to the current non-canonical plastids. We observed a clear difference in the contribution of VI-type proteins across the three pathways. In both Karenia/Karlodinium and Lepidodinium, we observed a substantial contribution of VI-type proteins to the isoprene and heme biosynthesises. In sharp contrast, VI-type protein was barely detected in the Chl a biosynthesis in the three dinoflagellates. Discussion Pioneering works hypothesized that the ancestral kareniacean species had lost the photosynthetic activity prior to haptophyte endosymbiosis. The absence of VI-type proteins in the Chl a biosynthetic pathway in Karenia or Karlodinium is in good agreement with the putative non-photosynthetic nature proposed for their ancestor. The dominance of proteins with haptophyte origin in the Karenia/Karlodinium pathway suggests that their ancestor rebuilt the particular pathway by genes acquired from the endosymbiont. Likewise, we here propose that the ancestral Lepidodinium likely experienced a non-photosynthetic period and discarded the entire Chl a biosynthetic pathway prior to the green algal endosymbiosis. Nevertheless, Lepidodinium rebuilt the pathway by genes transferred from phylogenetically diverse organisms, rather than the green algal endosymbiont. We explore the reasons why green algal genes were barely utilized to reconstruct the Lepidodinium pathway.
Keywords: Endosymbiosis; Organellogenesis; Plastid; Endosymbiotic gene transfer; Lateral gene transfer; Haptophytes; Green algae; Plastid replacement